Depression moderates the association between pregnancy and suicidal ideation among pregnant and non-pregnant reproductive age women in Brazil - Faisal-Cury, Alexandre; Tabb, Karen M.; Maruyama, Jessica Mayumi; Matijasevich, Alicia (Frontiers in Psychiatry, 2022)
Background: Maternal mental health problems are a serious public health concern. Previous data reported that pregnancy might have a protective effect against suicide. In contrast, more recent studies suggested that the prevalence of suicidal ideation (SI) is higher among pregnant women compared to the general population. Using a nationally representative population-based sample of Brazilian reproductive-aged women, this study aims to assess whether SI is more prevalent among pregnant women in comparison with nonpregnant woman. Methods: We used data from the Brazilian National Health Survey (PNS) of 2019, a cross-sectional study that comprised a representative sample of residents in private households in Brazil. For the analysis of this study, we selected women aged between 15 and 49 years old who have answered the questionnaire of the Selected Resident of the PNS, which comprised a sample of 27,249 women. Logistic regression models were performed to obtain crude and adjusted odds ratios (OR) and 95% confidence intervals (95%CI) for the association between pregnancy status and SI. Results: The prevalence of SI during pregnancy was 6.8% (95% CI: 6.2-7.4). The association between pregnancy status and SI was modified according to the recent clinical diagnosis of depression (interaction term: OR = 41.72, 95% CI: 5.64-308.45, p < 0.001). Our findings indicated that among nondepressed women, pregnancy status seems to decrease the probability of SI. Additionally, SI is associated with a vulnerable profile that includes being an adolescent, having an unpartnered/not married status, lower family income, lower education, and a recent clinical diagnosis of depression. Conclusion: SI is a common problem for reproductive-age women. In the presence of a recent depression clinical diagnosis, pregnancy increases the risk of SI. Management of SI among pregnant women should correctly identify sociodemographic risk factors and the presence of a recent clinical diagnosis of depression.